Holly Sims. Political Regimes, Public Policy and Economic Development: Agricultural Performance and Rural Change in the Two Punjabs. New Delhi: Sage Publications India Pvt. Ltd., 1988. 206 pp. Rupees (Indian) 175.00. (Hardbond Edition). (The Pakistan Development Review, 1990)
The book under review is a comparative study of agricultural development in the Indian (East) and Pakistani (West) Punjab. Although the growth of agricultural output and productivity in the two Punjabs was about the same between 1950 and 1965, it became significantly higher in East Punjab than West Punjab in the period that followed, with the result that the Indian Punjab enjoyed productivity levels in 1985 which were double those of the Pakistani Punjab. As the two Punjabs offer a sort of laboratory to gauge the agro-ecological conditions as well as the language and cultural traditions, any differences in their development experience must be explained by reference to the divergent economic policies towards agriculture followed there. Sims thinks that development experiences of the two Punjabs can be attributed to a political dichotomy and the consequent role of the political leadership in the formulation of economic policies. In the case of Pakistan, the Muslim League lacked mass support in the rural areas. Its middle class forces and political institutions were weak, with a predominance of landed aristocracy and bureaucrats. As a consequence, there was hardly any zest for democratic rule. By contrast, the Congress Party, under the charismatic leadership of Nehru, enjoyed full support of the rural masses. At the national level, it was devoid oflanded interests and created a new administrative class to run government affairs.